Revolutionizing repertoires : the rise of populist mobilization in Peru - Jansen, Robert S., 1977- (The University of Chicago Press, 2017)
Politicians and their political parties tend to act in routine ways, rarely deviating from conventional practice in a given time and place. Where, then, do new political practices come from? When new practices are developed, what shapes their characteristics? And what does it take for them to get assimilated into the toolkit of routine go-to options? Drawing on pragmatist theories of social action, this book elaborates a novel theoretical approach to these questions of political innovation. It then applies the approach to explain a critical development in Peruvian political history: the emergence in 1931 of a distinctively Latin American style of populist mobilization. Prior to Peru's 1931 presidential election, nothing like populist mobilization had been practiced in the country on a national scale to seek elected office; after this moment, the practice was an established option in the Peruvian political repertoire. Ultimately, populist mobilization emerged in Peru in 1931 because newly empowered outsider political actors had the socially and experientially conditioned understanding, vision, and capacities to recognize the limitations of routine political practice and to modify, transpose, invent, and recombine practices in a way that took advantage of new opportunities that were afforded by the social and political situation. This finding offers new insights to historians of Peru, students of historical sociology and contentious politics, and anyone interested in the social and political origins of populism.